The Impact of Supply Chain Management and Information Systems on Operational Performance: Empirical Evidence from SMEs in Saudi Arabia - Ahmad Hamed, Adel Abdellatif; Bohar, Abdul Manaf; Siam, Mohammed (International Journal of Supply Chain Management, 2017)
The study entails impact on operational performance (OPER) of small and medium size enterprises (SMEs) by using supply chain management (SCM) and information system (IS) practices in Saudia Arabia empirically. Moderation investigation of Supply Chain Management and Information System link promoted factors and impeding factors in implementing Supply Chain Management and Information System applies and OPER also taken in to account in the second part of the research. In the current study, underlying dimensions of SCM and IS practices are also empirically identified, and enabling and inhibiting fators related to SCM-IS are also identified at the first stage. Regression analysis was used for estimation of studying impact of variables on OPER and SMEs in the second phase of the research. Comparative results discussion have taken place in Saudi context at the end of the research. The study significantly contribute while considering and evaluating literature, acquire and analyses of collected data about Supply Chain Management and Information System implementations in Saudi Small and Medium Enterprices.